Recent Advances in Mechanisms of Plant Defense to Sclerotinia sclerotiorum - Wang, Zheng; Ma, Lu-Yue; Cao, Jun; Li, Yu-Long; Ding, Li-Na; Zhu, Ke-Ming; Yang, Yan-Hua; Tan, Xiao-Li (Frontiers in Plant Science, 2019)
Sclerotinia sclerotiorum (Lib.) de Bary is an unusual pathogen who has the broad host range, diverse infection modes and potential double feeding lifestyles of both biotroph and necrotroph. It is capable of infecting over 400 plant species found worldwide and more than 60 names have agriculturally been used to refer to diseases caused by this pathogen. Plant defense to S. sclerotiorum is a complex biological process and exhibits a typical quantitative disease resistance (QDR) response. Recent studies using Arabidopsis thaliana and crop plants have obtained new advances in mechanisms used by plants to cope with S. sclerotiorum infection. In this review, we focused on our current understanding on plant defense mechanisms against this pathogen, and set up a model for the defense process including three stages: recognition of this pathogen, signal transduction and defense response. We also have a particular interest in defense signaling mediated by diverse signaling molecules. We highlight the current challenges and unanswered questions in both the defense process and defense signaling. Essentially, we discussed candidate resistance genes newly mapped by using high-throughput experiments in important crops, and classified these potential gene targets into different stages of the defense process, which will broaden our understanding of the genetic architecture underlying quantitative resistance to S. sclerotiorum. We proposed that more powerful mapping population(s) will be required for accurate and reliable QDR gene identification.